Opportunistic bacteria and mass mortality in ungulates: lessons from an extreme event. Issue 6 (18th June 2019) - Robinson, Sarah; Milner‐Gulland, E. J.; Grachev, Yuri; Salemgareyev, Albert; Orynbayev, Mukhit; Lushchekina, Anna; Morgan, Eric; Beauvais, Wendy; Singh, Navinder; Khomenko, Sergei; Cammack, Rosie; Kock, Richard
Abstract: Mass mortality events in wildlife are a growing concern. Under conditions of rapid global change, opportunistic responses in bacterial commensals, triggered by environmental stressors, may be increasingly implicated in die‐offs. In 2015, over 200, 000 saiga antelope died of hemorrhagic septicemia caused by the pathogen Pasteurella multocida serotype B. We use this case to explore die‐offs from commensal bacteria more broadly, looking at factors which might favor such extreme events. We review other recorded disease outbreaks caused by Pasteurellaceae organisms, firstly in saiga and secondly in other wild ungulates, and ask whether the 2015 die‐off was unprecedented in terms of mortality rates, numbers dead, spatial scale, and in the nature of the predisposing or environmental factors involved. We also compare these outbreaks with mass mortality events associated with commensal bacteria in wildlife more generally. We identify three additional major die‐offs in saiga in which Pasteurellaceae organisms may be implicated, of which one in 1988 closely resembles the 2015 hemorrhagic septicemia event. No other recorded cases in wild ungulates approach the magnitude of these cases for any of the metrics considered, possible exceptions being die‐offs in Mongolian gazelles, in which the role of these pathogens is poorly substantiated. Environmental triggers were the most commonly suggested factor leading to pathogenesis, with warm humid conditions most commonly associated with hemorrhagic septicemia. Life history may also be significant—saigas are migratory and the largest pasteurellosis outbreaks outside this species also occur in migratory species of bird or other temperate ungulates aggregating in large numbers. Cases provoked by other commensals tend to be small in magnitude. Exceptions involve interactions between multiple pathogens and climatic conditions or sets of climatic conditions acting on different stages of the host–pathogen life cycle, leading to time lags between infection and subsequent disease. Overall, the scale and rapidity of the saiga die‐offs appear unprecedented among mortality events caused by bacterial commensals in wild mammals. Experimental research into the genetics and microbiology of host–pathogen interactions upon changes in the external environment, and monitoring of animals and conditions at calving sites, may eventually reveal the underlying causes of these die‐offs.